Daya Beli Masyarakat Pada Sektor Retail Menjelang Nataru Di Kota Rantauprapat - Henky Japina; Syamsinah Sirait; Rosnaida .; Helmina Simanjuntak (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2025)
This study aims to analyze the purchasing power of the community in the retail sector ahead of the Christmas and New Year (NATARU) celebrations in Rantauprapat City by examining the factors influencing purchasing power, including income, product quality, price, and business location. This research is a quantitative study with an explanatory research type, using a sample of 50 respondents who made purchases in the retail sector for NATARU celebrations. The partial results show that income, product quality, and business location have a positive and significant influence on purchasing power, while price has a negative and insignificant effect. Simultaneously, income, product quality, price, and business location have a positive and significant impact on purchasing power. The coefficient of determination value obtained is 78.2%, indicating that variations in purchasing power can be explained by income, product quality, price, and business location, while the remaining 21.8% is influenced by other factors not included in this research model. These findings indicate that increasing income, ensuring good product quality, and having a strategic business location can enhance purchasing power while maintaining competitive pricing to sustain consumer purchasing power.